Contribution of leading commodities to the economy of Sarolangun Regency, Jambi Province - Suandi Suandi; Dedy Hendry; Ajra Ajra; Syahrasaddin Syahrasaddin (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This study aims to analyze the contribution of leading commodities to the economy of Sarolangun Regency, Jambi Province. The data used are time series data from 2013-2017, the 2013-2017 GRDP of Sarolangun Regency, the 2013-2017 GRDP of Jambi Province and the 2013-2017 Sarolangun Regency population data. Data were descriptively analyzed using the Klassen typology approach. There were six prime sectors based on the calculation results through Klassen typology during 2013-2017, namely: (1) mining and excavating; (2) water supply, waste management, waste, and recycling; (3) financial services and insurance; (4) administration of government, defense, and mandatory social security; (5) health services and social activities; and (6) other services, while other sectors were classified as potential sectors, developed sectors, and underdeveloped sectors.